Korean national election study 1992 - Lee, Nam-Young; Cho, Joong-Bin (Institute for Korean Election Studies, 1992)
This survey was carried out immidiately after the Korean National Assembly election on March 24 and include questions on knowledge about candidate winning in the respondent's local district and which party the candidate represented, interest in the election campaign, attitude toward the candidates, voting decision, vote in the 1987 presidential election, and opinion on most serious problems in Korea. There were also a number of questions dealing with illegalities committed during the election campaign and with the clean election campaign run by the National Election Management Bureau. Background variables include information on age, gender, education, monthly income, size of household, housing, occupation, and place of residence.

Undersökningen genomfördes efter valet till den koreanska nationalförsamlingen den 24 mars 1992 och innehåller bland annat frågor om vilken kandidat som vann i respondentens distrikt och vilket parti han representerar; intresse för valkampanjen; inställning till kandidaterna och hur man själv röstade; samt erfarenhet av mutor och annan illegal verksamhet i samband med valkampanjen. Bakgrundsvariabler innehåller information om ålder, kön, utbildning, månadsinkomst, hushållsstorlek, bostad, sysselsättning, och bostadsort.
Korean national election study 1992
Keywords: Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap